Political and Legal Configurations Emergence of Laws Concerning Human Rights After the Fall of the Orde Baru Regime - Moh. Syafi`ie; Suparman Marzuki (Trigin Publisher, 2022)
This research was conducted using a legal sociology approach because it wanted to open a dialectical perspective from the political and legal constellation that occurred in Indonesia, both in the New Order regime era and in the transitional era towards democracy so that the Law on human rights emerged. Data collection was carried out using a literature study in the form of a literature review and a documentation study. While the data analysis was carried out in a qualitative descriptive manner (content analysis). The results of this study indicate that the existence of Law No. 39 of 1999 concerning Human Rights did not appear suddenly and from a critical awareness of the government, but was the result of a long struggle from the dynamics and political and legal struggles that existed in Indonesia during the authoritarian regime. the new order, pressure from the international community, as well as influencing the political and legal configuration after the fall of the New Order regime. The political and legal configurations of the New Order era were hegemonic, tyrannical and centralistic. The state becomes a terror power (state terrorism), a corporate state (state corporatism), a patron client state (state clientelism) and becomes a state that rules public opinion (state discourse). Systemic violations of human rights led to demands for total reform from the people which were very massive and demanded Suharto step down from the presidency. Meanwhile, politics and law in the post-New Order regime era were marked by a spirit of respect for human rights. The political configuration experienced liberalization and the law required reforms to be based on the universal values ​​of human rights. Departing from the sociological facts of the political and legal configuration of the New Order and its destruction towards a democratic transition (reform), the DPR/MPR political decree was realized in the form of TAP MPR No.XVII/MPR/1998 concerning Human Rights. This political decree is the soul of the emergence of the Act. No. 39 of 1999 concerning Human Rights, Law No. 26 of 2000 concerning the Human Rights Court, and other laws with dimensions of human rights in the reform era.